Integrating Concepts and Expressions of Inclusion in the K – Curriculum: The Case of the Philippines - Princess Zarla J. Raguindin* (European Journal of Educational Research, 2020)
Inclusive education as a curricular trend is implemented by countries as an action taken in response to the collective call of the Salamanca Statement. It carries the tenet that all learners should be educated alongside their peers regardless of physical, cognitive, socio-emotional, and economic, language, cultural, and other perceived differences. School children, as peers of children with special needs, are co-implementers of the inclusive agenda. Young children are competent, possess their views and agencies, and have nascent characteristics that promote inclusion. As such, it is essential to explore how knowledge, skills, attitudes, values, and ethics can further be developed and refined for the sake of creating an inclusive community through integrating them in the school curriculum. This paper sought to analyse the articulation of inclusive concepts and expressions in the K-curriculum and strategies utilized by the teachers to reinforce them. Two documents were analysed in this study to address the research questions: (a) prescribed k-curriculum currently used in the Philippines (b) interview transcripts of the key informants. Through content analysis, results of the study revealed that several inclusive concepts and expressions are articulated in the kindergarten curriculum across domains and are reinforced by teachers using varied strategies. Recommendations of the study are discussed.